THE INFLUENCE OF MICROWAVE RADIATION TO THE ELECTROPHYSICAL CHARACTERISTICS OF AU-TIB X –GAAS DIODE STRUCTURE - Kaypnazarov, S.G. (FAN va JAMIYAT, 2017)
It is defined that during the effecting time of microwave radiation to the Au-TiBx-GaAs diode structure for 0-20sc the structure parameters have improved. In the result of microwave the branchis temperature stability of this diode structure is shown. In the result of these factors the change of external curvature radius has been determined.